The Effectiveness of Olive Oil in Preventing Atherosclerosis: A Literature Review - Syamsu, Rachmat Faisal; Thahira, Yugni Maula; Nasruddin, Hermiaty; Dahlia, Dahlia; Indarwati, Rezky Putri; Palloge, Salahuddin Andi; Nurdin, Abbas Zavey; Makmun, Armanto; Bahar, Burhanuddin (Poltekkes Kemenkes Palu, 2024)
Olive oil is a rich source of oleic acid and polyphenols. Extra virgin olive oil is rich in phenolic compounds which are known to have anti-inflammatory, anti-cancer, and antioxidant effects. Olive oil has been used for thousands of years as a food source and is reported to have beneficial effects on cardiovascular disease. This review aims to provide a comprehensive overview of the current literature on the use of olive oil in the prevention and treatment of cardiovascular diseases and prevention of atherosclerosis. The methodology is employed by searching the article at Google Scholar, PubMed, Semantic Scholar, teaching materials, and research gate. Studies included the consumption of olive oil, by using qualitative and quantitative methodologies, were published in journals between 2013 and 2024 to obtain the latest information and relevant contents of the articles as well as the empirical data that indicate the effectiveness of olive oil. This research has a varying result, such as the high level of cholesterol and low-density lipoprotein cholesterol (LDL-C). Olive oil polyphenols also increase HDL particle size increase HDL stability by producing a triglyceride-poor core, and improve HDL antioxidant status by increasing the olive oil polyphenol metabolite content of lipoproteins, and it can intake of several foods also positively modulates platelet reactivity and may be the basis for the reduced cardiovascular risk reported in individuals on diets that increase the intake of plant foods, such as the Mediterranean diet. The olive oil which contains MUFA in the form of oleic acid and polyphenols has anti-atherogenic properties to prevent cardiovascular disease.